0026 Simulated Disclosure – Using An Interprofessional Medical Simulation Day To Develop Incident Disclosure. (1st November 2014) - Woodier, Nick; Buttery, Andrew; Baxendale, Bryn
Abstract : Background/context: When incidents occur, patients want full disclosure. 1 Disclosure can improve patient satisfaction and trust, and decrease the likelihood of patients seeking legal advice following errors. 2 Disclosure is a significant element of the safety culture 3 of organisations and by being open and honest staff can reduce the incidents of complaints, particularly those associated with poor communication and attitude. Methodology (used or planned): We conduct a series of interprofessional safety and simulation days for medical trainees. These days include trainees of all medical grades and nursing staff with whom they work. They receive high-fidelity simulation scenarios with aspects of Human Factors and safety. It is particularly utilised to explore error recovery and disclosure of incidents to simulated relatives. The disclosure by participants is recorded and discussed during the debrief. Participant attitudes and comfort with incident disclosure is surveyed before and after the day. Results/outcomes (to date): To date, 42 participants have successfully completed the simulation day and provided complete feedback. 98% of those who completed the survey agreed or strongly agreed that incident disclosure is an important part of the outcome after error and that communication is key to this (those who did not, did so by the end of the session). They were, however, less comfortable with how to disclose error and very few had received any training in the subject. The simulation day showed that 65% felt that their error disclosure communication skills had increased as a result of the day. Conclusions: Simulation is an ideal environment for practicing and testing the communication involved with incident disclosure. By incorporating local errors into scenarios with simulated patients and relatives, comes the opportunity to address this poorly taught skill. The next step is to see whether this learning is transferable to real clinical practice. References: Mazor KM, Simon SR, Gurwitz JH. Communicating with patients about medical errors: a review of the literature. Arch Intern Med 2004;164(15):1690–7 Mazor KM, Simon SR, Yood RA, et al . Health plan members' views about disclosure of medical errors. Ann Intern Med 2004;140:409–18 ECRI. Risk and Quality Management Strategies 21: Culture of safety. 2005